A scoping review of Australian allied health research in ehealth. Issue 1 (December 2016) - Iacono, Teresa; Stagg, Kellie; Pearce, Natalie; Hulme Chambers, Alana
Abstract Background Uptake of e-health, the use of information communication technologies (ICT) for health service delivery, in allied health appears to be lagging behind other health care areas, despite offering the potential to address problems with service access by rural and remote Australians. The aim of the study was to conduct a scoping review of studies into the application of or attitudes towards ehealth amongst allied health professionals conducted in Australia. Methods Studies meeting inclusion criteria published from January 2004 to June 2015 were reviewed. Professions included were audiology, dietetics, exercise physiology, occupational therapy, physiotherapy, podiatry, social work, and speech pathology. Terms for these professions and forms of ehealth were combined in databases of CINAHL (EBSCO), Cochrane Library, PsycINFO (1806 – Ovid), MEDLINE (Ovid) and AMED (Ovid). Results Forty-four studies meeting inclusion criteria were summarised. They were either trials of aspects of ehealth service delivery, or clinician and/or client use of and attitudes towards ehealth. Trials of ehealth were largely from two research groups located at the Universities of Sydney and Queensland; most involved speech pathology and physiotherapy. Assessments through ehealth and intervention outcomes through ehealth were comparable with face-to-face delivery. Clinicians used ICT mostly for managing their work and for professional development, but were reticent about its use in service delivery, which contrasted with the more positive attitudes and experiences of clients. Conclusion The potential of ehealth to address allied health needs of Australians living in rural and remote Australia appears unrealised. Clinicians may need to embrace ehealth as a means to radicalise practice, rather than replicate existing practices through a different mode of delivery.